2023
DOI: 10.18235/0004741
|View full text |Cite
|
Sign up to set email alerts
|

Is there discrimination against children of same-sex households? Evidence from an experimental study in Colombia

Abstract: We measure the extent of discrimination against same-sex couples by schools in Colombia using a matched-pair correspondence study. We send requests to visit private schools from several couples of different sexual orientation as conveyed by the names of the parents. We track the response rate from schools, the time to reply and the quality of the reply. We find that schools are 12 percentage points (22.3%) less likely to respond to a request sent by a homosexual couple with respect to one sent by a heterosexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[18] On the other hand, evidence from a field experiment conducted in Colombia suggests that discrimination in the educational sphere also extends to the children of homosexual spouses. [19] In this study, fake requests were made to visit private educational centers in the country, with the names of the spouses selected at random to convey information about the couple's sexual orientation (gay, lesbian, and heterosexual). The experiment found that, on average, schools were 12 percentage points less likely to respond to a request sent by a homosexual couple than one sent by a heterosexual couple.…”
Section: Access To Educationmentioning
confidence: 99%
“…[18] On the other hand, evidence from a field experiment conducted in Colombia suggests that discrimination in the educational sphere also extends to the children of homosexual spouses. [19] In this study, fake requests were made to visit private educational centers in the country, with the names of the spouses selected at random to convey information about the couple's sexual orientation (gay, lesbian, and heterosexual). The experiment found that, on average, schools were 12 percentage points less likely to respond to a request sent by a homosexual couple than one sent by a heterosexual couple.…”
Section: Access To Educationmentioning
confidence: 99%